Effects of anxiety sensitivity on alcohol problems: evaluating chained mediation through generalized anxiety, depression and drinking motives. (23rd October 2014) - Allan, Nicholas P.; Albanese, Brian J.; Norr, Aaron M.; Zvolensky, Michael J.; Schmidt, Norman B.
Abstract Aims To test whether the relations between anxiety sensitivity (AS), a transdiagnostic risk factor, and alcohol problems are explained by chained mediation models, from AS through anxiety or depressive symptoms then drinking motives in an at‐risk sample. It was hypothesized that AS would influence alcohol problems through generalized anxiety or depression symptoms and then through negatively reinforced drinking motives (i.e. drinking to cope with negative affect and drinking to conform). Design Cross‐sectional single‐ and chained‐mediation models were tested. Setting Self‐report measures were completed in clinics at Florida State University and the University of Vermont, USA. Participants Participants consisted of 523 adult daily cigarette smokers [mean age = 37.23, standard deviation (SD) = 13.53; 48.6% female]. Measurements As part of a larger battery of self‐report measures, participants completed self‐report measures of AS, generalized anxiety, depression, drinking motives and alcohol problems. Findings Chained mediation was found from AS to alcohol problems through generalized anxiety then through drinking to cope with negative affect [B = 0.04, 90% confidence interval (CI) = 0.004, 0.10)]. Chained mediation was also found from AS to alcohol problems through depression then through drinking to cope with negative affect (B = 0.11, 90% CI = 0.05, 0.21) and, separately, through socially motivated drinking (B = 0.05, 90% CI = 0.003, 0.11). Conclusions Anxiety sensitivity and alcohol problems are indirectly related through several intervening variables, such as through generalized anxiety or depression and then through drinking to cope with negative affect.